2020
DOI: 10.1007/s00068-020-01426-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diaphragm thickness on rehabilitation outcomes in post-ICU patients with spinal cord and brain injury

Abstract: Background Intensive care unit (ICU) complications affect outcomes but it remains unknown if the diaphragm thickness affects rehabilitation outcomes after ICU. We conducted a pilot study to evaluate the effect of diaphragm thickness on rehabilitation outcomes of post-ICU patients with spinal cord injury (SCI) and traumatic brain injury (TBI) and to evaluate factors that may be associated with diaphragm atrophy. Materials and methods Fifty-one patients (26 SCI, 25 TBI) who admitted to the rehabilitation clinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Diaphragm atrophy can easily be assessed by ultrasound in the ICU setting to predict weaning outcomes. 39 Patients without diaphragm atrophy have a higher rate of liberation from MV, 40 shorter ICU length of stay 41 and shorter MV time in the ICU setting. 7 , 9 , 13 , 42 - 44 Diaphragm ultrasound can assess diaphragm thickness, a known predictor of MV time.…”
Section: Discussionmentioning
confidence: 99%
“…Diaphragm atrophy can easily be assessed by ultrasound in the ICU setting to predict weaning outcomes. 39 Patients without diaphragm atrophy have a higher rate of liberation from MV, 40 shorter ICU length of stay 41 and shorter MV time in the ICU setting. 7 , 9 , 13 , 42 - 44 Diaphragm ultrasound can assess diaphragm thickness, a known predictor of MV time.…”
Section: Discussionmentioning
confidence: 99%
“…In anesthesiology, diaphragm ultrasound helps determine the residual muscle relaxation in patients under general anesthesia, addressing the complexities and interferences associated with the gold standard train-of-four ratio procedure ( 53 ), it is possible to predict and prevent postoperative pulmonary complications in surgical patients, including those undergoing heart surgery, thoracic surgery, and upper abdominal surgery ( 34 , 54–58 ). In rehabilitation medicine, diaphragm thickness is positively correlated with patients’ functional scores and functional independence scores before and after rehabilitation, suggesting that diaphragm thickness can influence patients’ rehabilitation progress ( 59 ). Overall, diaphragm ultrasound has become a valuable tool in routine clinical practice, particularly for assessing diaphragmatic function in various medical conditions.…”
Section: Ultrasound Evaluation Of Diaphragmatic Dysfunctionmentioning
confidence: 99%
“…3 In a pilot study, it was found that as many as 64% of patients with TBI had diaphragm atrophy. 4 The pathophysiology of VIDD is poorly understood. Studies have shown that increased proteolysis of muscle fibers, decrease blood supply to the diaphragm, or oxidative stress may be responsible for VIDD.…”
Section: Introductionmentioning
confidence: 99%